Phenomenal phenomena: biblical and multicultural accounts of spirits and exorcism - Vaughan, Joy L. (Baylor University Press, 2023)
"Examines New Testament accounts of spirit possession and exorcism in light of modern anthropological and ethnographic data of these phenomena"--